Upaya Pencegahan Kekerasan Seksual Pada Anak Melalui Pendidikan Kesehatan Reproduksi Sejak Dini - Zulfi Zumala Dwi Andriani; Amirotun Nahdliyah (IAI Darussalam, 2018)
Sexual abuse of children in Indonesia is becoming more prominent this time with a number of cases were aired by some media, data protection commission children and women in 2013 stated that cases of sexual violence to be the most dominant among other cases. Komnas children even mention the year 2013 as an emergency sexual crimes against children .According to data reported by P2TP2A Banyuwangi, cases of violence experienced by children in Banyuwangi in 2015 as many as 113 cases, and 13 of them occur in children under age. Until recently, this figure is still rising with the discovery of several cases of early 2016. The reproductive health education, and sexuality developed from early sex education should be taught to children as the bulwark preventing violence in children. To combat sexual violence on children, it is considered necessary given the knowledge about reproductive health education to the teachers and parents in the neighborhood kindergarten. Early childhood education at the kindergarten level is believed to be the starting point for the formation of character so that the material on the prevention of sexual abuse in children is very appropriate when administered at age kindergarten through teachers and parents. Key words : sexual abuse, children, sexual education